Biogas for climate justice: a story of change in Nepal - Manandhar, U.; Bhatta, Gopal Datt (2013)
Switching from a wood-fuelled cooking fire to a biogas flame saves trees and time, reduces greenhouse gas emissions and prevents health problems. Community-based cooperatives in the Terai plains of Nepal are using carbon credits to fund micro-loans for families to install the technology.